Effects of Methylphenidate on Attention in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
In a randomized, double-blind, placebo-controlled study of 60 children aged 8-12 years with ADHD treated with two doses of methylphenidate (MPH), 0.25 and 0.5 mg/kg, and placebo, a linear improvement was obtained at both doses in alertness and focused and sustained attention.